HUBUNGAN KONDISI LINGKUNGAN SEKOLAH DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA SISWA SMA NEGERI DI KOTA SANGGAU TAHUN 2014 - ., Dwi Yunia Ningsih (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. A healthy school environment was a kind of school environment which supported the community who stayed in there to havea hygienic and healthy life behavior. Until now, research on therelationship of school environmental condition with hygienic and healthylife behavior (PHBS), especially on high school students in the SanggauCity had never been done before. Objective. This study aimed to assessthe relationship of school environmental condition with hygienic andhealthy life behavior on high school students in Sanggau City 2014.Methodology. This study was an observational analytic study with crosssectionaldesign. This study was conducted at SMAN 3 Sanggau City onthe 3rd to 7th3 February 2014. School environmental condition wasassessed through observation and PHBS on students was assessed byquestionnaire. Respondents who were studied totaled to 120 studentsfrom SMAN 1, SMAN 2 and SMAN 3 Sanggau. Results. Two of the 3schools observed on their environmental conditions belonged to goodcategory (66.67 %) and another belonged to moderate categories (33.33%). Of the 120 students, 68 (56.67 %) students were included in goodcategory of PHBS and 52 (43.33 %) of students included in the badcategory. There was a significant relationship between schoolenvironmental condition with PHBS on high school students in SanggauCity 2014 (p = 0.009). Conclusion. School environmental condition affectPHBS on high school students in Sanggau City 2014 Keywords: school environmental condition, Hygienic and Healthy LifeBehavior (PHBS) Annotation:1. Medical Education Program, Faculty of Medicine, University of Tanjungpura Pontianak, West Kalimantan2. Public Health Department, Medical Education Program, Faculty of Medicine, University of Tanjungpura Pontianak, West Kalimantan3. Public Health Department, Medical Education Program, Faculty of Medicine, University of Tanjungpura Pontianak, West Kalimantan